The Effectiveness of The Principle of Consumer Recognition from Bank in Preventing The Crime of Money Laundering - Rafii Diaz Rasendriya; Aidul Fitriciada Azhari (Universitas Muhammadiyah Surakarta, 2023)
This journal entitled